Examining the health status of homeless adults entering permanent supportive housing. (17th June 2017) - Henwood, Benjamin F; Lahey, John; Rhoades, Harmony; Winetrobe, Hailey; Wenzel, Suzanne L
Abstract: Background: Permanent supportive housing (PSH) has been recognized as an effective intervention and the national policy for addressing chronic homelessness in the United States. Due to an aging cohort of homeless adults and prioritizing those who are most vulnerable for housing, the health status of those entering PSH is likely worse than those previously reported in the literature. Methods: This report examined the self-reported health and health conditions of a sample of 421 homeless adults entering PSH between 2014 and 2016. The average age of our sample was 54 years old. Results: Overall, 90% reported two or more chronic conditions (either physical or mental), 68% reported at least two chronic physical health conditions and 56% indicated at least two chronic mental health conditions. Describing their health status, 57% reported fair, poor or very poor health. Conclusions: These findings suggest that access to housing will not easily remedy the well-documented premature mortality among chronically homeless adults.